The beat! : go-go music from Washington, D.C. - Lornell, Kip, 1953- (American made music series., 2009)
The Beat! was the first book to explore the musical, social, and cultural phenomenon of go-go music. In this new edition, updated by a substantial chapter on the current scene, authors Kip Lornell and Charles C. Stephenson, Jr., place go-go within black popular music made since the middle 1970s--a period during which hip-hop has predominated. This styling reflects the District's African American heritage. Its super-charged drumming and vocal combinations of hip-hop, funk, and soul evolved and still thrive on the streets of Washington, D.C., and in neighboring Prince George's County, making it.